Aerodynamic characteristics of a cranked planform blended wing-body aircraft with 400 sweep angle - M Ahmad, A; E M Nasir, R; A A Latif, Z; Kuntjoro, W; Wisnoe, W; S Ishak, I (International Journal of Engineering and Technology, 2018)
Baseline 7 Blended Wing-Body design is introduced to study the behaviour of the control surfaces, given four elevons without vertical stabilizer and wingtip. The objective of the paper is to obtain an aerodynamic characteristic of a cranked planform blended wing-body aircraft. The airfoil used for the entire body is NACA 2412, which is selected for ease of fabrication process. The wingspan of the model is 1.4 m with 0.2 m thickness. The sweep angle of the model is fixed to 400. The wingspan area is calculated at 0.405 m2. The experiment is conducted at UTM-LST Wind Tunnel, AEROLAB, Skudai, Johor with test wind speed of 15 m/s. The maximum lift-to-drag ratio for the model is found to be around 21.9, which is better than many conventional aircraft. Nonetheless, the parabolic regression made to the drag versus lift plot only yields maximum lift-to-drag ratio of 10.0. The value of drag coefficient at zero lift is 0.012 while the maximum lift coefficient found is at 0.65 at 150 angle of attack. The lift-to-drag ratio improves 38.3% from 15.9 in the previously-published design. The neutral point is found to be located at 30.6% of the mean geometric chord in front of the wind tunnel model reference center or about 0.398 m from the nose of the 0.63 m long aircraft model or at 63.1% of aircraft length from the nose.Â Â